Lesotho : Sixth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Lesotho's Sixth Review Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Nonobservance of Performance Criteria. Real GDP growth slowed to 3u percent in 2003/04 (April-March) owing to the adverse impact of drought on agricultural output and slower-than-envisaged growth in the construction sector. Fiscal performance in 2003/04 was stronger than envisaged in the program, partly reflecting temporary factors. All quantitative performance criteria for December 2003 and indicative targets for March 2004 were met. The IMF staff supports the key macroeconomic objectives of the authorities' budget for 2004/05.